The Malagasy Mountain Programme: Understanding Madagascar's High-Elevation Systems Under Global Change - V. Ralph Clark; Steven M. Goodman; Jay le Roux; Fanomezana Mihaja Ratsoavina; Mijoro Rakotoarinivo; Peter John Taylor; Voahangy Soarimalala; Andrinajoro R. Rakotoarivelo (Mountain Research and Development)
Worldwide, high-elevation and high-latitude systems are experiencing the effects of global change faster than elsewhere, but there are limited data on the rate and impact of this change in Malagasy mountains. Reaching 2876 m, these mountains are some of the least-studied areas on the island of Madagascar. The Malagasy Mountain Programme aims to attract greater national and international interest in Malagasy mountains as social-ecological systems and is designed as a net for cooperative research, practitioner interventions, and policy impacts. As a small start, the Programme is a collaborative partnership between the Afromontane Research Unit (University of the Free State, South Africa), Association Vahatra (Madagascar), and the University of Antananarivo (Departments of Plant Biology & Ecology and Zoology & Animal Biodiversity, Madagascar). Additional partnerships are being developed, and more are welcomed.